2013
DOI: 10.1371/journal.pone.0053931
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypermethylation of ARID1A Gene Is Responsible for Its Low mRNA Expression in Many Invasive Breast Cancers

Abstract: ARID1A (AT-rich interactive domain 1A) has recently been identified as a tumor suppressor gene. Its mRNA expression is significantly low in many breast cancers; this is often associated with more aggressive phenotypes. However, the underlying molecular mechanism for its low expression has not been fully understood. This study was undertaken to evaluate the contribution of gene copy number variation, mutations, promoter methylation and histone modification to ARID1A’s low expression. 38 pairs of breast invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 22 publications
2
51
0
3
Order By: Relevance
“…Although ARID1A mutation frequency in breast cancer appears to be modest (some 4%; ref. 6), ARID1A loss may be caused via other mechanisms, such as promoter hypermethylation and DNA copy number loss (41)(42)(43). However, our data do not rule out the possibility that induction of ANXA1 levels is also caused by oncogenic signaling pathways that are independent of ARID1A loss.…”
Section: Discussionmentioning
confidence: 60%
“…Although ARID1A mutation frequency in breast cancer appears to be modest (some 4%; ref. 6), ARID1A loss may be caused via other mechanisms, such as promoter hypermethylation and DNA copy number loss (41)(42)(43). However, our data do not rule out the possibility that induction of ANXA1 levels is also caused by oncogenic signaling pathways that are independent of ARID1A loss.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, Zhang et al . reported that promoter hypermethylation of the ARID1A gene is responsible for its low mRNA expression in many invasive breast cancers 25. These findings encouraged us to score the ARID1A immunoreactivity of invasive breast cancer to evaluate the prognosis value of ARID1A in invasive breast cancers.…”
Section: Discussionmentioning
confidence: 96%
“…This explanation may be viable, as CpG islands have been identified on the ARID1A promoter and ARID1A promoter hypermethylation has been reported recently in invasive breast cancer. 38 However, several other studies have shown that ARID1A loss of expression is strongly associated with mutations in the ARID1A gene, and for endometrial cancer, the mutation rate corresponds with the frequency of ARID1A loss. 4,6,12,26 Moreover, promoter hypermethylation as inactivating mechanism of the ARID1A gene has not been reported in endometrial cancer.…”
Section: Modern Pathology (2013) 26 1525-1535mentioning
confidence: 96%